PERJANJIAN BELI KEMBALI (BUY BACK GUARANTEE) YANG DIBUAT ANTARA PENGEMBANG DAN BANK DALAM PENYELESAIAN MASALAH KREDIT MACET - Dominika, Retno Wahyurini; Kawuryan, Endang Sri (Faculty of Law, University of Dr. Soetomo, 2017)
The type of research used in this study is normative legal research, which according to Peter Mahmud Marzuki,